Determination of Uric Acid in Biological Fluids with Special Emphasis on Biosensors and Sensors: A Review - Pundir, Chandra S.; Kumari, Seema; Ravina; Pundir, Shikha (International Journal of Applied Sciences and Biotechnology, 2025)
Uric acid is produced in human liver from the breakdown of dietary purines and purine compounds into xanthine, which is oxidized by xanthine oxidase to generate uric acid. Since uric acid is the end product of purine breakdown in human, it is discharged through gut and kidneys. The normal uric acid levels in blood are 0.202- 0.416mM in males and 0.142- 0.357mM in females. The increased level of uric acid in serum and urine is viewed as a significant biomarker for gout, hyperuricemia, and renal-disorders, while low uric acid levels affect brain and spinal cord. The determination of unusual uric acid level in blood and urine is required for the differential conclusion and restorative administration of gout, hypertension, cardiovascular ailments, renal infection & Lesch– Nyhan disorder and recently type-2 diabetes. The conventional techniques for uric acid determination are muddled, nonspecific, less touchy and require tedious example pretreatment, costly instrumental set-up and trained people to work, explicitly for chromatographic techniques. The biosensors defeat these downsides, as these are basic, quick, explicit and very sensitive and specific. The uric acid biosensors work ideally within 3–180 s, between5.5–8.5 pH, temperature 22°C - 37°C and uric acid concentration 10-2000mM. These biosensors have been employed to measure uric acid level in serum, urine and saliva, reused up to 200-times within 7–216 days. The future perspectives of uric acid biosensors are discussed. Int. J. Appl. Sci. Biotechnol. Vol 13(3): 100-122.